Experimental Study on the Rheological Mechanical Properties and Creep Mechanism of Red Mudstone in Central Yunnan - Wang, Bo; Ding, Yushu (Scientific Journal of Technology, 2026)
To explore the creep characteristics and mechanism of soft rock from a microscopic perspective, this paper investigates the red mudstone from the Shizishan tunnel section in central Yunnan. A stepwise loading approach was employed to investigate the creep characteristics of the rock samples. A viscous model was established in the 3D particle flow code (PFC), and the discrete element method (DEM) was employed to simulate static fatigue failure of the rock based on experimental data, thereby studying its microscopic creep mechanism. The results show that: (1) Under low stress conditions, the rock samples primarily exhibit decelerating creep, where creep deformation accounts for up to 85% of the total deformation. Under high stress conditions, the rock samples experience the entire creep process, transitioning from decelerating creep, to steady-state creep, and finally to accelerated creep failure, with creep deformation accounting for up to 87% of the total deformation; (2) Shear stress levels significantly affect the creep deformation of rock samples, with a positive correlation between shear stress levels and the time required for decelerating creep to reach a stable state. The proportion of creep deformation in total deformation increases correspondingly; (3) As lateral stress levels increase, the creep strain rate gradually rises. If the stress exceeds the threshold, irreversible stress damage occurs, shortening the creep time; (4) By inserting measurement circles to monitor the coordination number during the loading process, the relationship between porosity and shear mechanism can be determined. The model’s overall fit is high, and the behavior of the 3D model during stepwise loading is essentially consistent with that under single-step loading, validating the reliability of the experiment.